1987
DOI: 10.1139/y87-346
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in tissue antioxidant systems in the spontaneously diabetic (BB Wistar) rat

Abstract: Tissue antioxidant status in insulin-dependent spontaneously diabetic BB Wistar rats (ISDBB), diabetes-prone nondiabetic littermates (NDLM), and weight-matched non-BB control Wistar rats was investigated in pancreas, heart, and liver, as well as kidney. Pancreatic activities of CuZn-superoxide dismutase and glutathione reductase (GSSG-RD) were higher in ISDBB rats, while catalase (CAT) activities were elevated in both ISDBB and their NDLM compared with control animals. On the other hand, pancreatic reduced glu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
24
0

Year Published

1988
1988
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 13 publications
2
24
0
Order By: Relevance
“…Cardiac tissue exposed to ambient high glucose may initially mount a defense response by augmenting the antioxidant system. In fact, the levels of GSH in STZ-induced or insulin-dependent spontaneously diabetic rats were elevated in the heart (40,41), although there are some reports showing the opposite results (42,43). Such discrepancy in the cardiac GSH among the diabetic models may be due to the duration of hyperglycemia at the time when the GSH level was measured.…”
Section: Discussionmentioning
confidence: 98%
“…Cardiac tissue exposed to ambient high glucose may initially mount a defense response by augmenting the antioxidant system. In fact, the levels of GSH in STZ-induced or insulin-dependent spontaneously diabetic rats were elevated in the heart (40,41), although there are some reports showing the opposite results (42,43). Such discrepancy in the cardiac GSH among the diabetic models may be due to the duration of hyperglycemia at the time when the GSH level was measured.…”
Section: Discussionmentioning
confidence: 98%
“…Prior studies using cardiac tissue or cardiomyocytes from animal models of diabetes demonstrated upregulation of antioxidant enzymes (14), increased production of hydrogen peroxide (41), and increased lipid peroxidation (12,13). Recently, oxidative stress in diabetic human hearts has been shown (42) by the finding of elevated levels of the marker of oxidative damage, nitrotyrosine, in biopsies from diabetic patients.…”
Section: Discussionmentioning
confidence: 99%
“…The heart is a susceptible target because it contains low levels of free radical scavengers (11). Available evidence implicating ROS in diabetic cardiomyopathy include increased cardiac lipid peroxidation (12,13) and elevated expression of genes for the antioxidants catalase (12,14,15) and heme oxygenase (16). Also, functional or morphological damage to diabetic hearts can be reduced with oral or systemic antioxidant administration (12,17).…”
mentioning
confidence: 99%
“…It has been reported that increased free-radical mediated oxidative stress is associated with diabetic complications in both humans and animals [4,[12][13][14][15][16]. Reactive Oxygen Species (ROS) or Free Oxygen Radicals (FOR's) such as superoxide radical (O 2 -), hydroxyl radical (OH -), and hydrogen peroxide (H 2 O 2 ), generated during oxygen metabolism, are controlled by various cellular defense mechanisms consisting of enzymatic [(superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GSHPx)] and non-enzymatic (vitamin E, β-carotene, vitamin C) antioxidants [17].…”
Section: Introductionmentioning
confidence: 99%